2007
DOI: 10.1103/physrevb.76.014421
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling through magnetic molecules with arbitrary angle between easy axis and magnetic field

Abstract: Inelastic tunneling through magnetically anisotropic molecules is studied theoretically in the presence of a strong magnetic field. Since the molecular orientation is not well controlled in tunneling experiments, we consider arbitrary angles between easy axis and field. This destroys all conservation laws except that of charge, leading to a rich fine structure in the differential conductance. Besides single molecules we also study monolayers of molecules with either aligned or random easy axes. We show that de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
(77 reference statements)
0
33
0
Order By: Relevance
“…An example is provided by the differential conductance calculated in Ref. [11] for a magnetic molecule with magnetic anisotropy axis not aligned with the applied magnetic field, where N = 20, but due to noncommuting terms in the Hamiltonian many rates are nonzero and are distributed over a broad range.…”
Section: Introductionmentioning
confidence: 99%
“…An example is provided by the differential conductance calculated in Ref. [11] for a magnetic molecule with magnetic anisotropy axis not aligned with the applied magnetic field, where N = 20, but due to noncommuting terms in the Hamiltonian many rates are nonzero and are distributed over a broad range.…”
Section: Introductionmentioning
confidence: 99%
“…General derivations of these equations have recently appeared in the literature (Elste and Timm, 2005;Koller et al, 2010;Leijnse and Wegewijs, 2008) together with several approximate solutions applied to SETs with quantum dots (Weinmann et al, 1995) and molecules (Koller et al, 2010;Leijnse and Wegewijs, 2008;Leijnse et al, 2009) including SMMs (Elste and Timm, 2005Timm, 2007;Timm and Elste, 2006). The simplest strategy is to solve these equations perturbatively in the tunneling Hamiltonian (Bruus and Flensberg, 2004).…”
Section: Hamiltonian Of the Transport Devicementioning
confidence: 98%
“…Recently, a great deal of effort has been paid to study quantum transport through SMMs both theoretically and experimentally [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The experiment of electron transport through the Mn 12 attached with nonmagnetic electrodes has shown that the macroscopic quantum tunneling of the SMM plays an important role due to breaking symmetry [3].…”
Section: Introductionmentioning
confidence: 99%